Dampak Globalisasi Digital terhadap Identitas Budaya Generasi Muda: Kajian Literatur - Maria Renyaria Kali; Dwisye M. B. Poyck; Welfranal Chorianty Abe; Margareta Ebong Hurek; Gerardus Mayorga; Trenchy A. M. D. Balu; Rista Apriliya Devi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Digital globalization has brought significant changes to the cultural identity of the younger generation, particularly in the way they interact, access information, and shape cultural patterns in the modern era. The rapid development of social media, communication technologies, and global cultural flows has increased young people's exposure to foreign cultures, leading to shifts in the values and meanings of local cultures. This study aims to analyze the impact of digital globalization on the cultural identity of the younger generation and to describe the forms of cultural change that occur in the digital era. The study employed a qualitative approach using a literature review method. Data were collected through the identification, review, and analysis of various relevant sources, including books, scientific journals, and scholarly articles related to the research topic. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that digital globalization has both positive and negative impacts on the cultural identity of the younger generation. Positive impacts include easier access to cultural information and increased creativity in utilizing digital media, while negative impacts include the declining use of local cultures and regional languages, as well as lifestyle changes influenced by foreign cultures. The study concludes that digital globalization significantly affects the cultural identity of the younger generation. Therefore, efforts to preserve local culture through education, family involvement, and the wise use of digital media are essential. The findings of this study are expected to serve as a foundation for strengthening cultural awareness and fostering a sense of pride in local culture among the younger generation.